Synovial Fluid Alpha-defensin Lateral Flow Assay is Specific but Not Sensitive for Periprosthetic Joint Infection in Revision Arthroplasty: A Propensity Score-matched Analysis - Sze Hon Yu; Chiu Kwong Yuen; Constance Wong; Cheung Amy; Cheung Man Hong; Chan Vincent Wai Kwan; Luk Michelle Hilda; Chan Ping Keung; Henry Fu (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Synovial fluid alpha-defensin lateral flow assay (ADLFA) is a quick adjunctive test in diagnosing periprosthetic joint infection (PJI) after primary arthroplasty. However, evidence is lacking for postrevision arthroplasty cases. Thus, we investigated the performance of ADLFA in revision cases and compared it to a control cohort of primary arthroplasty cases. Methods: One hundred eleven suspected PJI cases with previous total knee or hip arthroplasty between 2017 and 2021 were retrospectively included; they were minimally followed up for 12 months after joint aspiration. Cases were stratified into the revision and control (primary) group using propensity score matching in a 1:2 ratio. The 2018 Musculoskeletal Infection Society criteria were the gold standard for PJI and the Delphi-based consensus criteria for persistent infection. Results: After matching, the two groups exhibited comparable baselines. The sensitivity and specificity for revision cases were 50.0% (95% confidence interval [CI] =23.0%–77.0%) and 100.0% (95% CI = 83.2%–100.0%), respectively, and for primary cases, it was 75.0% (95% CI = 55.1%–89.3%) and 100.0% (95% CI = 90.3%–100.0%), respectively. Thus, ADLFA was less sensitive for revision arthroplasty but equally specific for both primary and revision cases. Furthermore, the sensitivity for ADLFA varied considerably between revision surgeries for septic causes and aseptic causes, but specificity remained 100.0%. Conclusion: ADLFA was highly specific but not sensitive in diagnosing PJI in postrevision arthroplasty cases. It is suited as a convenient confirmatory adjunct alongside the existing criteria.